2021
DOI: 10.1016/j.sajb.2020.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Honey bees are important pollinators of South African blueberries despite their inability to sonicate

Abstract: Honey bees, Apis mellifera, are important pollinators of the highbush blueberry variety Ventura despite the inability to sonicate Honey bees are important pollinators of blueberries despite their inability to sonicate

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Nevertheless, buzz-pollinating bees are often more efficient pollinators as shown in eggplant ( Hikawa 2004 ), blueberry and cranberry ( Stubbs and Drummond 1996 , Javorek et al 2002 ), kiwifruit ( Pomeroy and Fisher 2002 , Kim et al 2005 ), and tomato ( Banda and Paxton 1991 ). In blueberries, for example, honey bees can visit flowers to collect nectar ( Javorek 2002 ), and these managed non-buzzing bees can be used to pollinate this crop ( Martin et al 2019 ). However, honey bees are inefficient pollinators of blueberries, requiring four times more visits to transfer the same amount of pollen compared to buzz-pollinating bees ( Javorek 2002 ).…”
Section: Which Crops Are Buzz Pollinated?mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, buzz-pollinating bees are often more efficient pollinators as shown in eggplant ( Hikawa 2004 ), blueberry and cranberry ( Stubbs and Drummond 1996 , Javorek et al 2002 ), kiwifruit ( Pomeroy and Fisher 2002 , Kim et al 2005 ), and tomato ( Banda and Paxton 1991 ). In blueberries, for example, honey bees can visit flowers to collect nectar ( Javorek 2002 ), and these managed non-buzzing bees can be used to pollinate this crop ( Martin et al 2019 ). However, honey bees are inefficient pollinators of blueberries, requiring four times more visits to transfer the same amount of pollen compared to buzz-pollinating bees ( Javorek 2002 ).…”
Section: Which Crops Are Buzz Pollinated?mentioning
confidence: 99%
“…However, honey bees are inefficient pollinators of blueberries, requiring four times more visits to transfer the same amount of pollen compared to buzz-pollinating bees ( Javorek 2002 ). The sheer abundance of honey bees in well stocked fields may, in some cases, balance their inefficiencies leading to adequate pollination ( Lomond and Larson 1983 , Aras et al 1996 , Dedej and Delaplane 2003 , Martin et al 2019 ). Yet, when honey bees are not abundant visitors to blueberries, visitation by wild bees, including buzz pollinators, improves fruit yield and fruit quality ( Nicholson and Ricketts 2019 ).…”
Section: Which Crops Are Buzz Pollinated?mentioning
confidence: 99%
“…To determine pollination deficits and benefits of bees to the five varieties, we followed the methods of Martin et al (2021). Below we provide a brief description.…”
Section: Methodsmentioning
confidence: 99%
“…One crop where honey bees are thought to be less effective than other pollinators is blueberries. Wild and commercial blueberries are extremely reliant on insect pollination (Aras et al, 1996; MacKenzie, 1997; Dogterom et al, 2000; Fulton et al, 2015; Martin et al, 2021) and are typically pollinated by large bees. These include blueberry bees (Apidae) (Cane and Payne, 1993; Campbell et al, 2018), bumble bees (Apidae) (Mackenzie and Eickwort, 1996; Stubbs and Drummond, 2001; Javorek et al, 2002; Tuell et al, 2009; Campbell et al, 2017), and mining bees (Andrenidae) (Mackenzie and Eickwort, 1996; Javorek et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Research carried out in Burkina Faso, indicated that the negative consequence of any pollinator decline can cause an average yield gap of 37% for cotton production, and 59% in sesame production (Stein et al 2017). These yield gaps in pollination services can be calculated for each crop by comparing the fruit yields in the presence of different pollinator communities (Garibaldi et al 2016) or by comparisons between open natural pollination (mixed self-and cross-pollination), outcrossing hand pollination and pollinator exclusion (Hudewenz et al 2013;Martin et al 2021). Yield gaps effectively estimate the potential to improve crop yields by optimizing the pollination environment.…”
Section: Importance Of Pollination Services and Pollinator Conservatimentioning
confidence: 99%